1976
DOI: 10.1055/s-0028-1104097
|View full text |Cite
|
Sign up to set email alerts
|

Hämoglobin-M-Homburg

Abstract: Haemoglobin M is a rare cause of congenital cyanosis and is usually misdiagnosed as being due to congenital heart disease. This was also the case in a family on whom this report is based. In five members of three generations the characteristic grey-blue cyanosis was due to a haemoglobin M anomaly. In all of them cardiopulmonary disease, anaemia and haemolysis had been excluded. The amino-acid substitution was in the alpha-chain of the globin molecule. Consequently the carriers of the trait have an abnormal hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…20,21 Destruction of the b cells results in a decrease in production of insulin and IAPP causing type 2 diabetes (T2D). 22,23 Extensive biophysical and computational studies have indicated that short sequence fragments with high aggregation propensity may promote the amyloidogenic propensity of a protein. 15,16 Numerous, extensive studies focused on "aggregation-prone" segments have been performed in the case of hIAPP.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Destruction of the b cells results in a decrease in production of insulin and IAPP causing type 2 diabetes (T2D). 22,23 Extensive biophysical and computational studies have indicated that short sequence fragments with high aggregation propensity may promote the amyloidogenic propensity of a protein. 15,16 Numerous, extensive studies focused on "aggregation-prone" segments have been performed in the case of hIAPP.…”
Section: Introductionmentioning
confidence: 99%